Gambaran Faktor-Faktor Pemberian Vitamin A Pada Balita Di Puskesmas Kecamatan Muara Satu Kota Lhokseumawe Tahun 2020 - M. Fikri Haikal; Yuziani Yuziani; Mardiati Mardiati (Pusat Riset dan Inovasi Nasional, 2024)
Vitamin A has biological activity as retinol that can increase the body's resistance to infectious diseases so that it can reduce morbidity and mortality due to vitamin A deficiency, and has an important role for eye health. Vitamin A deficiency (VAD) is the main cause of blindness in children, Aceh Province ranks the fourth lowest in giving vitamin A, it is estimated 30 million toddlers in Indonesia aged 12-59 months, half of whom suffer from VAD. The role of mothers in giving vitamin A is very important, several factors influence the giving of vitamin A to children, that is the level of mother's education, mother's knowledge, mother's visit to Posyandu, mother's job, and the distance from the mother's house to the Posyandu. The purposes of this research are to know the description of mother's education level, mother's knowledge, mother's visit to Posyandu, mother's job, and distance from mother's house to Posyandu in Muara Satu Subdistrict Health Center, Lhokseumawe City. This research method uses a descriptive approach with cross sectional design and sampling using consecutive sampling technique, for data collection is using primary and secondary data. The results of the research on the description of the factors of giving vitamin A at the Muara Satu Subdistrict Health Center, Lhokseumawe City, find that the mother's education level is low 78.1%, mother's knowledge is less 66.8%, mother's visit to Posyandu is high 53.1%, mother does not have a job 88.4%, and the distance from the mother's house to the Posyandu is near 65.6%. The conclusions of this study are the level of mother's education is low, the mother's knowledge is less, the mother's visit to Posyandu is high, the mother's does not have a job, and the distance between the mother's house to Posyandu is near, these variables are a description of the factors of giving vitamin A at Muara Satu Subdistrict Health Center, Lhokseumawe City.